OFFENSIVE AUTOMATICS, DKS CONCEPT - Dzikic, Aleksandar; Mihajlovic, Filip (Sport- és Egészségtudományi füzetek, 2025)
Talking about offensive concept, some people call it reads when they react to the defense, talking about higher levels we can call it automatics, this basically means faster, more accurate and more precise execution. This system must be incorporated very early in the season so that the players can understand their position, their timing on the court. The es-sential rules of offense are basically more space and fewer players on one certain area of the court.